2021
DOI: 10.1097/01.aoa.0000766020.37448.96
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Reproductive Health of Young Women and Cardiovascular Disease in Later Life: Umbrella Review

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 125 publications
(188 reference statements)
1
24
0
2
Order By: Relevance
“…Use of oral contraceptive pills is associated with stroke in young women; one recent systematic review and meta-analysis demonstrated an odds ratio (OR) of 2.47 for use of any type of oral contraceptive, although when broken down by formulation, combined oral contraceptives remained significant while progesterone-only pills were not associated with increased risk. 46…”
Section: Risk Factors For Strokementioning
confidence: 99%
“…Use of oral contraceptive pills is associated with stroke in young women; one recent systematic review and meta-analysis demonstrated an odds ratio (OR) of 2.47 for use of any type of oral contraceptive, although when broken down by formulation, combined oral contraceptives remained significant while progesterone-only pills were not associated with increased risk. 46…”
Section: Risk Factors For Strokementioning
confidence: 99%
“…A recent meta-analysis found that PCOS was associated with a 30% higher risk of overall CVD (odds ratio [OR], 1.30 [95% CI, 1.09–1.56]), including both coronary heart disease (CHD; OR, 1.44 [95% CI, 1.13–1.84]) and stroke (OR, 1.36 [95% CI, 1.09–1.70]). 35 A recent Danish registry found 19% increased risk of incident CVD (adjusted HR, 1.19 [95% CI, 1.07–1.33]) for women with PCOS, but this association was not seen in women after age 50 years. 36 Women with PCOS are also ≈3-fold more likely to develop APOs, including gestational diabetes mellitus (GDM) and preeclampsia, which in turn predict increased CVD risk.…”
Section: Polycystic Ovary Syndrome and Cvd Riskmentioning
confidence: 99%
“…Similar associations have been observed for subclinical atherosclerosis and clinical CVD events. 35 In the SWAN (Study of Women’s Health Across the Nation) Heart Study, women who did not breastfeed had elevated risks of aortic calcification (adjusted OR, 3.85 [95% CI, 1.47–10.00]) and CAC (adjusted OR, 2.78 [95% CI, 1.05–7.14]) compared to women who breastfed each child for ≥3 months, even after adjustment for demographic and lifestyle factors. 123 In the Nurses’ Health Study, women with ≥2 years of cumulative breastfeeding versus no breastfeeding had 23% (95% CI, 6%–38%) lower adjusted risk of CHD events.…”
Section: Breastfeeding and Cvd Risk Reductionmentioning
confidence: 99%
“…Preeclampsia pregnancies increase the likelihood of adverse pregnancy events, notably fetal growth restriction (FGR), and also increase the risk of cardiovascular diseases for both mother and offspring post-pregnancy. 4–7 Therefore, preeclampsia is currently recognized as a significant contributor to overall cardiovascular disease burden. 8 Preeclampsia is characterized by a prohypertensive milieu including endothelial dysfunction, 9,10 immune dysfunction, 11–13 and altered renin-angiotensin aldosterone system activation.…”
mentioning
confidence: 99%